Analytical Assessment of the Effect of Vertical Ground Motion on RC Frames Designed for Gravity Loads with Various Geometric Configurations - Siyun Kim; Sung Jig Kim; Chunho Chang (Advances in Civil Engineering)
The paper presents an analytical investigation of the effect of vertical ground motion on the selected 13 reinforced concrete (RC) frames with different geometric configurations. For this purpose, earthquake ground motions with various vertical-to-horizontal peak acceleration ratios are selected to which a suitable scale factor is applied to match with seismic hazards of Korea. The methodology involves the evaluation of the structural responses of RC frames subjected to the selected records by means of nonlinear time history analyses. The results from the analysis are compared with results from studies of the case of horizontal-only excitation. The effect of the vertical earthquake component on damage of RC frames is considered at both the global and the local levels. The effect of vertical ground motion on axial force, shear demand, and shear capacity of RC columns is investigated to assess failure on a local level. In particular, the shear capacity is evaluated by using both the conservative method of a design code and more realistic predictive approaches. The results of the extensive analyses indicate that vertical ground motion can significantly affect the response of RC members in terms of axial force variation and shear capacity. These results point to the conclusion that vertical ground motion needs to be included in analysis for assessment and design.